Influ??ncia da qualidade do trabalho em equipe no sucesso de projetos de software - Pires, Daniel de Lima (2017)
Software projects are increasingly prominent in today's organizational environment. Its use refers to increased efficiency, improvements in products and services, and also the technological strategy of organizations. They are technically complex, do not have physical limitations and are intangible, nevertheless they are very ambitious and surrounded by uncertainties. Software projects teams must deal with a large amount of information, in addition to making intensive use of knowledge of several areas simultaneously, and also must be skilled in communicating and coordinating their actions. In this dissertation, a quantitative approach research using Structural Equation Modeling with Partial Least Squares (PLS-SEM) was carried out to evaluate the relationship between Teamwork quality and software projects success. The Teamwork quality is a construct that allows measuring the internal collaboration of the team within six dimensions: mutual support, contribution balancing, cohesion, communication, coordination and effort. Software projects success is a widely studied construct in the scientific literature, and in this dissertation was considered as composed of efficiency, impact on the consumer and impact on the team. The result obtained showed that the Teamwork quality exerts considerable influence on the software projects success, corroborating the results of previous academic research, and generating the knowledge that the collaboration should be fostered by the organizations in software development teams. In addition, as a contribution to practice, a model was proposed to evaluate the software project teams teamwork quality, aiming to increase the internal collaboration of the project team and, consequently, the success of the software project.